Peran Personal Development Competitive Attitude dan Organizational Citizenship Behavior Terhadap Manajemen Konflik pada Karyawan Event Organizer - Puspita, Natalie; Kurniawan, Jimmy Ellya (Psychopreneur Journal, 2021)
The dynamic phenomenon of EO requires collaboration between members to run events, especially when facing conflicts that arise. The collaborative conflict management style can be referred to as a solution-orientation conflict management. In connection with this phenomenon, personal development competitive attitude and organizational citizenship behavior is known to play a role in improving conflict management solution-orientation among EO employees. This research is a quantitative study with multiple regression design. The population of this study were event organizer employees in Surabaya. The sample in this study amounted to 114 event organizer employees obtained through online surveys. The sampling technique used accidental sampling. This study uses a personal development competitive attitude scale (PDCA) designed by Ryckman et al. (1996), Organizational Citizenship Behavior Scale (OCB) designed by Podsakof et al. (1990), and the Organizational Communication Conflict Instrument (OCCI) designed by Putnam et al. (1982). The results of hypothesis testing state the role of personal development competitive attitude and organizational citizenship behavior in conflict management solution-orientation. In this study the variable organizational citizenship behavior has a bigger role than personal development competitive attitude. The results of the research can be used as knowledge and input for the company and EO employees.